An analysis of medical risk inspections in the context of the Office of Health Standards Compliance (OHSC) - Carstens, Pieter Albert, 1960- (University of Pretoria, 2022)
Mini Dissertation (MPhil (Medical Law and Ethics))--University of Pretoria, 2021.